(untitled) (Journal of Civil Engineering Researchers, 2025)
Due to the importance of bridges as vital arteries and the huge investment of countries in building bridges, the need for more accurate seismic analysis of bridges to better understand their structural behavior is inevitable. Like many structures, the effect of the rotational components of the earthquake on bridges has been less noticed by researchers and designers. This research has evaluated the effect of the rotational components of the earthquake to better understand the seismic behavior of bridge. For this purpose, in addition to three translational components, the rotational components of the earthquake, including two rocking components and one torsional component, have been considered in the three-dimensional seismic analysis of box-girder concrete bridges. By creating the rotational component of the earthquake by the Hong-Nan Li method, three box-girder bridges with pier heights of 12, 30, and 45 meters were subjected to the combined effect of six translational and rotational components, as well as three translational components were separately subjected to under a far-field earthquake with different soil and shear wave velocity. The results of the analysis show that the effect of the earthquake’s rotational components on the response of stresses and displacement, depending on the type of earthquake and the characteristics of the bridge structure, can be particularly important.